Processes and Recommendations for Creating mHealth Apps for Low-Income Populations - Stephan, Laura Siga; Dytz Almeida, Eduardo; Guimaraes, Raphael Boesche; Ley, Antonio Gaudie; Mathias, Rodrigo Gonçalves; Assis, Maria Valéria; Leiria, Tiago Luiz Luz (JMIR Publications, 2017)
BackgroundMobile health (mHealth) apps have shown to improve health indicators, but concerns remain about the inclusion of populations from low- and medium-income countries (LMIC) in these new technologies. Atrial fibrillation (AF) is a chronic condition with a challenging management. Previous studies have shown socioeconomic differences in the prescription of anticoagulant treatment and shared decision strategies are encouraged to achieve better outcomes. mHealth can aid both doctors and patients in this matter. ObjectiveWe describe the development of an mHealth app (aFib) idealized to aid shared decision between doctor and patient about anticoagulation prophylaxis in AF in a low-income and low-literacy population in Brazil. On the basis of our research, we suggest the processes to be followed when developing mHealth apps in this context. MethodsA multidisciplinary team collected information about the target population and its needs and detected the best opportunity to insert the app in their current health care. Literature about the subject was reviewed and important data were selected to be delivered through good navigability, easy terminology, and friendly design. The app was evaluated in a multimethod setting. ResultsThe steps suggested to develop an mHealth app target to LMIC are: (1) characterize the problem and the target user, (2) review the literature, (3) translate information to knowledge, (4) protect information, and (5) evaluate usability and efficacy. ConclusionsWe expect that these recommendations can guide the development of new mHealth apps in LMIC, on a scientific basis.